Penerapan Posisi Lateral 30 Derajat dan Massage Menggunakan Virgin Cocunut Oil (VCO) Terhadap Risiko Kerusakan Integritas Kulit Pada Pasien Stroke - Ni Made Ridla Nilasanti Parwata; Dewi Nurviana Suharto (Madago Nursing Journal, 2022)
Background: Non-Hemorrhagic Stroke is a dysfunction of the central nervous system in the form of blockage of brain blood vessels which results in hemiparesis, indirectly experiencing immobilization at risk of skin integrity damage, one of the independent nursing interventions in overcoming the risk of skin integrity damage is the provision of a lateral 30 position degrees and massage using Virgin Coconut Oil (VCO). Research Methods: Descriptive with a case study approach. Results: After the implementation for 4 days by giving a 30 degree lateral position and massage using virgin coconut oil 2 times a day. The application of a 30 degree lateral position and maage using virgin coconut oil can reduce the risk of skin integrity damage in stroke patients. Conclusion: The application of a 30 degree lateral position and massage using virgin coconut oil is effective in reducing the occurrence of skin integrity damage. Suggestion: It is hoped that it can provide independent nursing interventions as a companion to pharmacological therapy to overcome nursing problems that exist in non-hemorrhagic stroke patients.